Validation of the blood pressure measurement technology used in the Novacor Diasys 3 (DIS-0001-00) upper arm device for ambulatory blood pressure measurement, according to the requirements of the AAMI/ANSI/ISO 81060-2: 2013 standard (for both a general study and a cardiac-stress study in adults) and of the European Society of Hypertension International Protocol revision 2010. Issue 1 (February 2021) - Atkins, Neil; Fania, Claudio; Palatini, Paolo
Abstract : Objective: The objective of this study was to determine the accuracy of the oscillometric blood pressure measurement technology of the Novacor Diasys 3 (model number DIS-0001-00) blood pressure monitor, intended for ambulatory blood pressure measurement, when used with the recommended Standard (ACC-0213-00), Large (ACC-0214-00) and Paediatric (ACC-0215-00) cuffs. Methods: The Novacor Diasys 3 (model number DIS-0001-00) was evaluated according to the requirements of the AAMI/ANSI/ISO 81060-2:2013 standard, including an additional cardiac-stress study, a requirement for ambulatory blood pressure measurement devices. It was also validated according to the requirements of the European Society of Hypertension International Protocol revision 2010. The protocol requirements for all thee studies were followed precisely. Results: The Novacor Diasys 3 (model number DIS-0001-00) fulfilled all of the requirements for a pass in each of the three studies. In the primary AAMI/ANSI/ISO 81060-2:2013 study, the Criterion 1 errors were +3.9 mmHg ± 2.9 mmHg for SBP and +3.4 ± 2.5 mmHg for DBP. Conclusion: The Novacor Diasys 3 (model number DIS-0001-00), when used with the recommended cuffs, can be recommended for ambulatory blood pressure measurement in the adult population.